2018
DOI: 10.1007/s00439-018-1876-1
|View full text |Cite
|
Sign up to set email alerts
|

Inferring causal relationships between phenotypes using summary statistics from genome-wide association studies

Abstract: Genome-wide association studies (GWAS) have successfully identified numerous genetic variants associated with diverse complex phenotypes and diseases, and provided tremendous opportunities for further analyses using summary association statistics. Recently, Pickrell et al. developed a robust method for causal inference using independent putative causal SNPs. However, this method may fail to infer the causal relationship between two phenotypes when only a limited number of independent putative causal SNPs ident… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
1

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 42 publications
(68 reference statements)
0
3
0
Order By: Relevance
“…Previous investigations have delineated the relationships between blood metabolites and bone mineral density (BMD). For instance, one study pinpointed 10 blood metabolites that may influence femoral neck BMD ( Meng et al, 2018 ). Subsequently, another analysis revealed eight blood metabolites with a significant impact on hip BMD ( Liu et al, 2018 ), while a more recent study identified 13 plasma metabolites that markedly affect heel BMD ( Chen et al, 2023 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous investigations have delineated the relationships between blood metabolites and bone mineral density (BMD). For instance, one study pinpointed 10 blood metabolites that may influence femoral neck BMD ( Meng et al, 2018 ). Subsequently, another analysis revealed eight blood metabolites with a significant impact on hip BMD ( Liu et al, 2018 ), while a more recent study identified 13 plasma metabolites that markedly affect heel BMD ( Chen et al, 2023 ).…”
Section: Introductionmentioning
confidence: 99%
“…Now that large-scale genome-wide association studies (GWAS) data on GM, blood metabolites, and OP are publicly available ( Visscher et al, 2017 ), these resources afford a unique opportunity to explore the causal relationships between these variables using MR. Few studies have employed MR methods to explore the causal relationship between GM and OP ( Tu et al, 2021 ). While numerous studies have utilized MR to investigate the connection between blood metabolites and BMD ( Liu et al, 2018 ; Meng et al, 2018 ; Yu et al, 2022 ; Chen et al, 2023 ; Chen and He, 2023 ), research focusing specifically on the OP phenotype is scant. Moreover, comprehensive investigations into the associations among GM, blood metabolites, and OP remain limited.…”
Section: Introductionmentioning
confidence: 99%
“…Osteoporosis is a complex disease that prevalently occurs in postmenopausal women and is diagnosed primarily by measuring bone mineral density (BMD) ( Tella and Gallagher, 2014 ). Low femoral neck (FNK) BMD is a major risk factor of osteoporosis and remains the best predictor of primary osteoporotic fractures ( Meng et al, 2018 ). It is established that there are differences of genetic determination among various skeletal sites ( Yang et al, 2006 ).…”
Section: Introductionmentioning
confidence: 99%